Role based access control for knowledge sharing in remote areas - Usino, Wendi; Mantoro, Teddy; Ayu, Media Anugerah; Harjanto, Nazir (2011)
Many years ago, the Indonesian Government encouraged people from Java to migrate to other islands in order to enhance their living standard. In the case of Pasir Region, East Kalimantan, the 100 families who moved were originally from Jepara. Jepara is a very famous area of craft products and carving furniture. The problem is that they have to change their livelihood from a crafter to a farmer and lack the necessary original skills. This paper introduces a Role Based Access Control (RBAC) for e-Village in creating and sharing knowledge in a secure way. This includes secure information about marketing to help the products become an innovation and highly valuable. It also discusses and analyses the secure knowledge sharing and knowledge creating using e-village, not only for supporting the market development but also preserving the village culture more, especially in crafting and carving furniture. This study shows that the RBAC of e-village contributes significantly to the quality of knowledge for people in a remote area such as the Pasir Region village.